2013
DOI: 10.1371/journal.pone.0076189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Isoniazid Resistance on the Treatment Outcomes of Smear Positive Re-Treatment Tuberculosis Patients in the State of Andhra Pradesh, India

Abstract: BackgroundMulti drug resistant and rifampicin resistant TB patients in India are treated with the World Health Organization (WHO) recommended standardized treatment regimens but no guidelines are available for the management of isoniazid (INH) resistant TB patients. There have been concerns that the standard eight-month retreatment regimen being used in India (2H3R3Z3E3S3/1H3R3Z3E3/5H3R3E3; H-Isoniazid; R-Rifampicin; Z-Pyrazinamide; E-Ethambutol; S-Streptomycin) may be inadequate to treat INH resistant TB case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 7 publications
0
27
2
Order By: Relevance
“…During the initial period of our transplant program (40 liver transplants), the significance and management of these healed granulomas in the explanted liver were debated because no clear guidelines were available. Clinical equipoise existed because potentially up to 40% to 70% of Indians were likely to have healed occasional granulomas in their tissues, infection was often remote, immunosuppression after transplantation was lifelong (whereas isoniazid prophylaxis lasted 9 months), and there were high rates of reported isoniazid resistance by M. tuberculosis . When 2 of these index patients developed posttransplant TB, we re‐evaluated our protocol to initiate isoniazid prophylaxis for 9 months at 6 weeks after transplantation for all patients with granulomas in the explanted liver without an alternative cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initial period of our transplant program (40 liver transplants), the significance and management of these healed granulomas in the explanted liver were debated because no clear guidelines were available. Clinical equipoise existed because potentially up to 40% to 70% of Indians were likely to have healed occasional granulomas in their tissues, infection was often remote, immunosuppression after transplantation was lifelong (whereas isoniazid prophylaxis lasted 9 months), and there were high rates of reported isoniazid resistance by M. tuberculosis . When 2 of these index patients developed posttransplant TB, we re‐evaluated our protocol to initiate isoniazid prophylaxis for 9 months at 6 weeks after transplantation for all patients with granulomas in the explanted liver without an alternative cause.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical equipoise existed because potentially up to 40% to 70% of Indians were likely to have healed occasional granulomas in their tissues, infection was often remote, immunosuppression after transplantation was lifelong (whereas isoniazid prophylaxis lasted 9 months), and there were high rates of reported isoniazid resistance by M. tuberculosis. 24 When 2 of these index patients developed posttransplant TB, we re-evaluated our protocol to initiate isoniazid prophylaxis for 9 months at 6 weeks after transplantation for all patients with granulomas in the explanted liver without an alternative cause. This was thought to be adequate to reduce the risk of reactivation during the period when the intensity of immunosuppression was highest.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies from a variety of settings (with and without adjustment for treatment regimen and other confounders) have found similar results, including the previously cited study examining deaths in TB meningitis patients. 10;32;33 Other studies have not found an association between resistance and negative outcomes. 34;35 A large retrospective cohort of patients receiving short course chemotherapy from six countries was also less clear cut, showing an association between INH resistance and the risk of treatment failure in retreatment cases and weaker statistical evidence among new cases.…”
Section: The Influence Of Resistance On Treatment Outcomesmentioning
confidence: 98%
“…Individuals were classified as symptomatic if they had a cough for over 2 weeks, weakness, chest pain, and fever for over 1 month or hemoptosis on any occasion over six months [8]. Gene expert is used in the detection of MDR-TB [9].…”
Section: Methodsmentioning
confidence: 99%